Degradation of nonylphenol ethoxylate-10 (NPE-10) by mediated electrochemical oxidation (MEO) technology - Setiyanto, Henry; Syaifullah, Muhammad Muslim; Adyatmika, I Made; Dian Ayu Setyorini,; Azis, Muhammad Yudhistira; Zulfikar, Muhammad Ali; Vienna Saraswaty, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nonylphenol ethoxylate (NPE-10) is a non-ionic surfactant that is synthesized from alkylphenol ethoxylate. The accumulation of NPE-10 in wastewater will endanger the ecosystem as well as the human being. Nowadays, NPE-10 can be degraded indirectly by using an electrochemical treatment by the advancement of technology. Thus, this study is aimed to evaluate the electro-degradation potential of NPE-10 by MEO using Ce(IV) ionic mediator. In addition, the influence of Ag(I) ionic catalyst in the performance of MEO for the degradation of NPE-10 was also observed. The potency of MEO technology in the NPE-10 degradation was evaluated by voltammetry technique and confirmed by titrimetry and LC-MS analysis. The results showed that in the absence of Ag(I) ionic catalyst, the degradation of NPE-10 by MEO was 85.93%. Furthermore, when the Ag(I) ionic catalyst was applied, the performance of MEO in degradation of NPE-10 was improved to 95.12%. The back titration using Ba(OH)2 confirmed the formation of CO2 by 46.79%, whereas the redox titration shows the total of degradation organic compounds by 42.50%. It was emphasized by the formation of two new peaks in the LC-MS chromatogram. In summary, our results confirmed the potential of MEO technology for the NPE-10 degradation.